Institution-based barriers to innovation in SMEs in China - Zhu, Y.; Wittmann, X.; Peng, Mike (Springer New York LLC, 2012)
Despite significant development, small and medium-sized enterprises (SMEs) in China continue to experience institution-based barriers, especially in the area of innovation. What exactly are these barriers? How do these barriers influence innovation? How about the status quo of the institutional environment for SMEs' innovation and development? We seek to uncover these underexplored areas by developing a model characterized by a cost-risk-opportunity (CRO) innovation triangle. We then enrich this model by interviewing 82 top managers and owners at 41 SMEs. We identify the five key institution-based barriers to innovation in China: (1) competition fairness, (2) access to financing, (3) laws and regulations, (4) tax burden, and (5) support systems. These findings enhance the institution-based view of entrepreneurship by shedding light on how institution-based barriers affect innovation in SMEs.